Development of an immunoassay for the simultaneous detection of GADA and ZnT8A in autoimmune diabetes using a ZnT8/GAD65 chimeric molecule - Trabucchi, Aldana; Bombicino, Silvina Sonia; Sabljic, Adriana Victoria; Marfía, Juan Ignacio; Targovnik, Alexandra Marisa; Iacono, Rubén Francisco; Miranda, María Victoria; Valdez, Silvina Noemí (Frontiers in Immunology, 2023)
The combined presence of autoantibodies to the 65 kDa isoform of glutamic acid decarboxylase (GADA) and to the islet-specific cation efflux transporter ZnT8 (ZnT8A) in serum is the best predictive sign of the loss of immune tolerance and the clinical manifestation of autoimmune diabetes mellitus (DM). The screening of GADA and ZnT8A could help to reach to a correct diagnosis and to start an early and adequate treatment. The aim of the study was to develop an immunoassay for the simultaneous detection of these autoantibodies using a chimera molecule that includes the immunodominant regions of ZnT8 and GAD65, expressed by baculovirus-insect cells system.Materials and Methods: ZnT8/GAD65 was expressed using the Bac to Bac™ baculovirus expression system. The recombinant chimera was purified by an His6-tag and identified by SDS-PAGE and western blot analysis, and by an indirect ELISA using specific antibodies against ZnT8 and GAD65. A fraction of ZnT8/GAD65 was biotinylated. A bridge ELISA (b-ELISA) was developed using ZnT8/GAD65 immobilized in polystyrene microplates, human sera samples from healthy individuals (n = 51) and diabetic patients (n = 49) were then incubated, and afterwards ZnT8/GAD65-biotin was added. Immune complexes were revealed with Streptavidin-Horseradish Peroxidase. Results were calculated as specific absorbance and expressed as standard deviation scores: SDs.Results: ZnT8/GAD65 was efficiently produced, yielding 30 mg/L culture medium, 80% pure. This recombinant chimera retains the immunoreactive conformation of the epitopes that are recognized by their specific antibodies, so it was used for the development of a high sensitivity (75.51 %) and specificity (98.04 %) b-ELISA for the detection of ZnT8A and/or GADA, in a onestep screening assay. The ROC curves demonstrated that this method had high accuracy to distinguish between samples from healthy individuals and diabetic patients (AUC = 0.9488); the cut-off value was stablished at 2 SDs.This immunoassay is useful either to confirm autoimmune diabetes or for detection in routine screening of individuals at risk of autoimmune DM. As DM is a slow progress disease, remaining asymptomatic for a long preclinical period, serological testing is of importance to establish a preventive treatment.